Spanish Public Policies towards the Promotion of Cloud Computing and Digital Services for SMEs - Silvia Serrano Calle; Jorge Pérez Martínez; Zoraida Frías Barroso (International Telecommunications Society (ITS), 2016)
The paper focuses on the first public programs in Spain to support the introduction of cloud computing services for small and medium-sized enterprises (SMEs) and micro-SMEs, and facilitating the digital transformation of SMEs, stimulating e-commerce and encouraging competitiveness. The paper analyses how the programs that the Spanish Government launched in 2015 transcend technology and impact over the digital ecosystem, with influences over supply and demand. The paper identifies the main drivers of SMEs providing cloud services and ICT solutions and other key elements that help to understand the eligible portfolio of cloud solutions and authorised providers that will contribute to the digital transformation of Spanish SMEs and micro-SMEs.
Keywords: H76; L88; O14; 330; Digital Economy; Cloud Computing; SME; Public Policy